Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure! Let's solve the given expression step-by-step.
We need to simplify the left-hand side and the right-hand side of the equation:
[tex]\[ \frac{5^{3x} \times 25}{5^x} = 5^3 \times 125 \][/tex]
### Step 1: Simplify the Left-Hand Side
1. Rewrite [tex]\(25\)[/tex] and simplify:
Since [tex]\(25\)[/tex] can be written as [tex]\(5^2\)[/tex], the expression now becomes:
[tex]\[ \frac{5^{3x} \times 5^2}{5^x} \][/tex]
2. Apply exponents rule:
Using the exponent rule [tex]\(a^m \times a^n = a^{m+n}\)[/tex], we combine the exponents in the numerator:
[tex]\[ \frac{5^{3x + 2}}{5^x} \][/tex]
3. Simplify the fraction:
Using the exponent rule [tex]\( \frac{a^m}{a^n} = a^{m-n} \)[/tex], we subtract the exponent in the denominator from the exponent in the numerator:
[tex]\[ 5^{(3x + 2) - x} = 5^{2x + 2} \][/tex]
### Step 2: Simplify the Right-Hand Side
1. Rewrite [tex]\(125\)[/tex]:
Knowing [tex]\(125\)[/tex] is [tex]\(5^3\)[/tex], we write:
[tex]\[ 5^3 \times 125 = 5^3 \times 5^3 \][/tex]
2. Combine exponents:
Again, using the exponent rule [tex]\(a^m \times a^n = a^{m+n}\)[/tex]:
[tex]\[ 5^3 \times 5^3 = 5^{3 + 3} = 5^6 \][/tex]
### Step 3: Comparing Both Sides
Comparing the simplified forms of both sides,
- Left side: [tex]\( 5^{2x + 2} \)[/tex]
- Right side: [tex]\( 5^6 \)[/tex]
If these sides are equal, their exponents must be equal:
[tex]\[ 2x + 2 = 6 \][/tex]
### Solve for [tex]\(x\)[/tex]:
Solve the equation [tex]\(2x + 2 = 6\)[/tex]:
[tex]\[ 2x + 2 = 6 \][/tex]
[tex]\[ 2x = 6 - 2 \][/tex]
[tex]\[ 2x = 4 \][/tex]
[tex]\[ x = 2 \][/tex]
Thus, the value of [tex]\( x \)[/tex] that satisfies the given expression is [tex]\( x = 2 \)[/tex].
To validate this result numerically, the initial equation can be evaluated as follows:
[tex]\[ \left(\frac{5^{3 \cdot 2} \times 25}{5^2} = 5^3 \times 125\right) \][/tex]
[tex]\[ \left(\frac{5^6 \times 25}{5^2} = 5^3 \times 125\right) \][/tex]
[tex]\[ \left(\frac{5^6 \times 5^2}{5^2} = 5^3 \times 5^3\right) \][/tex]
[tex]\[ 5^6 = 5^6 \][/tex]
This confirms the correctness of the derived value [tex]\( x = 2 \)[/tex].
We need to simplify the left-hand side and the right-hand side of the equation:
[tex]\[ \frac{5^{3x} \times 25}{5^x} = 5^3 \times 125 \][/tex]
### Step 1: Simplify the Left-Hand Side
1. Rewrite [tex]\(25\)[/tex] and simplify:
Since [tex]\(25\)[/tex] can be written as [tex]\(5^2\)[/tex], the expression now becomes:
[tex]\[ \frac{5^{3x} \times 5^2}{5^x} \][/tex]
2. Apply exponents rule:
Using the exponent rule [tex]\(a^m \times a^n = a^{m+n}\)[/tex], we combine the exponents in the numerator:
[tex]\[ \frac{5^{3x + 2}}{5^x} \][/tex]
3. Simplify the fraction:
Using the exponent rule [tex]\( \frac{a^m}{a^n} = a^{m-n} \)[/tex], we subtract the exponent in the denominator from the exponent in the numerator:
[tex]\[ 5^{(3x + 2) - x} = 5^{2x + 2} \][/tex]
### Step 2: Simplify the Right-Hand Side
1. Rewrite [tex]\(125\)[/tex]:
Knowing [tex]\(125\)[/tex] is [tex]\(5^3\)[/tex], we write:
[tex]\[ 5^3 \times 125 = 5^3 \times 5^3 \][/tex]
2. Combine exponents:
Again, using the exponent rule [tex]\(a^m \times a^n = a^{m+n}\)[/tex]:
[tex]\[ 5^3 \times 5^3 = 5^{3 + 3} = 5^6 \][/tex]
### Step 3: Comparing Both Sides
Comparing the simplified forms of both sides,
- Left side: [tex]\( 5^{2x + 2} \)[/tex]
- Right side: [tex]\( 5^6 \)[/tex]
If these sides are equal, their exponents must be equal:
[tex]\[ 2x + 2 = 6 \][/tex]
### Solve for [tex]\(x\)[/tex]:
Solve the equation [tex]\(2x + 2 = 6\)[/tex]:
[tex]\[ 2x + 2 = 6 \][/tex]
[tex]\[ 2x = 6 - 2 \][/tex]
[tex]\[ 2x = 4 \][/tex]
[tex]\[ x = 2 \][/tex]
Thus, the value of [tex]\( x \)[/tex] that satisfies the given expression is [tex]\( x = 2 \)[/tex].
To validate this result numerically, the initial equation can be evaluated as follows:
[tex]\[ \left(\frac{5^{3 \cdot 2} \times 25}{5^2} = 5^3 \times 125\right) \][/tex]
[tex]\[ \left(\frac{5^6 \times 25}{5^2} = 5^3 \times 125\right) \][/tex]
[tex]\[ \left(\frac{5^6 \times 5^2}{5^2} = 5^3 \times 5^3\right) \][/tex]
[tex]\[ 5^6 = 5^6 \][/tex]
This confirms the correctness of the derived value [tex]\( x = 2 \)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.